ALT flares during nucleotide analogue therapy are associated with HBsAg loss in genotype A HBeAg‐positive chronic hepatitis B. (6th March 2018) - Wong, Darren; Littlejohn, Margaret; Edwards, Rosalind; Jackson, Kathy; Revill, Peter; Gaggar, Anuj; Kitrinos, Kathryn; Subramanian, Mani; Marcellin, Patrick; Buti‐Ferret, Maria; Janssen, Harry; Gane, Ed; et al.
Abstract: Background: Alanine aminotransferase (ALT) flares during NA therapy are uncommon but occur. Evaluation of ALT flares during nucleos(t)ide analogue (NA) therapy is important as new immunomodulatory therapies for hepatitis B virus (HBV) are developed. We evaluated the association between ALT flares and HBsAg loss during long‐term therapy for genotype A CHB. Methods: This analysis included genotype A subjects from a phase III study of tenofovir vs adefovir in HBeAg‐positive HBV. ALT flare was defined as (i) a rise in ALT >2x ULN from normal ALT levels; or (ii) a rise in ALT >2x baseline ALT level. HBsAg response at week 384 was recorded as one of HBsAg loss vs HBsAg decline (≥1 log10 IU/mL decline) vs non‐response. The primary analysis evaluated the association between ALT flare and HBsAg response. Results: 54 subjects were included. 23/54 (43%) subjects experienced an on‐treatment ALT flare. 45% achieved an HBsAg reduction ≥1 log10 IU/mL, and of these 67% achieved HBsAg loss at a median of 102 weeks [IQR: 64‐156]. Flare was associated with HBsAg decline vs non‐response (67% vs 23%, P = .002), and were more common in subjects who achieved HBsAg loss vs non‐response (56% vs 23%), P = .049). There was a median delay of 56 weeks [IQR: 40‐80] between a flare and HBsAg loss. Conclusion: In genotype A subjects undergoing long‐term NA therapy, ALT flares predict for HBsAg response. The delay between ALT flare and HBsAg loss has implications for clinical trial design for early phase development of immunomodulatory strategies aiming for HBsAg loss.